ANALISIS STRATEGI PENINGKATAN PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN SERTA EFEKTIVITAS PENERIMAANNYA DI KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Mamuko, Eflin R.; Sondakh, Jullie J.; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2018)
District of Siau Tagulandang Biaro had just started ti implement this rural and urban property taxes policy since January 2015. The number of unrecorded tax objects and taxpayer unclearness becomes a challenge for the district SITARO in increasing land tax and rural and urban buildingsd (PBB-P2). The purpose of this study is to know the strategy undertaken by the district of SITARO in overcoming the obstacles of the manny objects of taxes that have not been recorded and the unclearness of taxpayers and know level of effectiveness acceptance land tax and rural and urban buildingsd (PBB-P2). This type of research is descritive. The results of the research show the strategies undertaen by the SITAROÂ district government is to re-register, update the data and deletion of data. The effectiveness level in 2015 is quite effective with the persenrage of 88% and in 2016 is effective with the percentage of 98%.Keywords: Land tax and Rural and Buildings, strategy, effectiveness